Commitment requests do not affect truth-telling in laboratory and online experiments - Cagala, Tobias; Glogowsky, Ulrich; Rincke, Johannes; Schudy, Simeon (Games and Economic Behavior, 2024)
Using a standard cheating game, we investigate whether the request to sign a no-cheating declaration affects truth-telling. Our design varies the content of a no-cheating declaration (reference to ethical behavior vs. reference to possible sanctions) and the type of experiment (online vs. offline). Irrespective of the declaration's content, commitment requests do not affect truth-telling, neither in the laboratory nor online. The inefficacy of commitment requests appears robust across different samples and does not depend on psychological measures of reactance.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Cheating; Commitment; Commitment request; Compliance; Lying; No-cheating declaration; No-cheating rule; Truth-telling